Hospitalised patients as stewards of their own antibiotic therapy: a qualitative analysis informing the strategic design of interventions to encourage shared decision-making in tertiary hospital settings in Singapore - Guo, Huiling; Lye, David Chien; Ng, Tat Ming; Somani, Jyoti; Kwa, Andrea Lay Hoon; Chung, Shimin Jasmine; Chow, Angela (Frontiers in Public Health, 2024)
Background Shared decision-making (SDM) on antibiotic therapy may improve antibiotic use in tertiary hospitals, but hospitalised patients are apprehensive about being involved in it. Understanding the facilitators and barriers to SDM can inform the design and implementation of interventions to empower these patients to engage in SDM on their antibiotic therapies. Methods We conducted qualitative interviews with 23 adult patients purposively sampled with maximum variation from the three largest tertiary-care hospitals in Singapore (April 2019─October 2020). Thematic analysis was conducted using the Theoretical Domains Framework and Capability, Opportunity, Motivation, Behaviour (COM-B) model to identify areas for intervention. Results Hospitalised patients lacked comprehensive knowledge of their antibiotic therapies and the majority did not have the skills to actively query their doctors about them. There was a lack of opportunities to meet and interact with doctors, and patients were less motivated to engage in SDM if they had a self-perceived paternalistic relationship with doctors, trusted their doctors to provide the best treatment, and had self-perceived poor knowledge to engage in SDM. To empower these patients, they should first be educated with antibiotic knowledge. Highlighting potential side effects of antibiotics could motivate them to ask questions about their antibiotic therapies. Environment restructuring, as facilitated by nurses and visual cues to nudge conversations, could create opportunities for interactions and motivating patients into SDM on their antibiotic therapies. Conclusion Education and environmental restructuring should be explored to empower hospitalised patients to engage in SDM on their antibiotic therapies.